The mathematic connection ability of pre-service teacher during online learning according to their learning style - Hardi Hardi; Wahyudi Wahyudi; Hardi Suyitno; Kartono Kartono; YL Sukestiyarno (OmniaScience, 2022)
Mathematic connection is one of the basic abilities someone must have in order to learn mathematic successfully. Mathematic connection helps someone to understand the function of mathematics, improving mathematic concept, determining the correlation among mathematic concepts, and identifying the application of mathematic in the surrounding environment. The most common issue occur regarding this case is that the mathematic connection ability of mathematic pedagogy students are considerably low that finally result to low learning outcome. Moreover, mathematic learning is conducted online during the COVID-19 pandemic. Not every lecturer is capable to conduct an online learning properly. As the result, it becomes harder for the students to learn mathematic, let alone finding mathematic connection. This study aims at describing the mathematic connection ability among the mathematic pre-service teacher during online and offline learning, comparing the ability between the students who undergo online and offline learning, and creating the visualizations of mathematic connection ability of mathematic pedagogy students who undergo online learning based on their learning style. This study implements mixed methods with explanatory sequential design. The technique and data collecting instrument are conducted in two ways, those are quantitative and qualitative data collection techniques. For the quantitative data (mathematic connection ability), it is measured through test, while the qualitative data is acquired using questionnaire and descriptive qualitative according to the category of mathematic connection ability. The findings obtained are the mathematic connection ability of the students. The findings present that the mathematic connection ability of students in online learning are better than those in offline learning (expository). Students with the tendency of having more than one learning style are better than those who only prefer one type of learning style (visual, auditory, kinaesthetic).